Age and blood pressure stratified healthy vascular aging, organ damage and prognosis in the community-dwelling elderly: insights from the North Shanghai Study - Ren, Zhongyuan; Yang, Haotian; Zhu, Wenqing; Han, Jun; Yu, Shikai; Zhao, Song; Meng, Weilun; Xu, Yawei; Zhao, Yifan; Zhang, Yi (Clinical hypertension, 2024)
Background This study aimed to investigate the prognostic value of age and blood pressure stratified healthy vascular aging (HVA) defined in the North Shanghai Study (NSS), and illustrate its relationship with organ damage (OD). Methods This study enrolled 3590 community-dwelling elderly Chinese aged over 65 years and finally 3234 participants were included. 3230 individuals were included in the final analysis, with 4 participants lost to follow-up. NSS HVA was defined as low carotid-femoral pulse wave velocity (PWV) which had a higher cutoff value with advanced age and level of blood pressure. OD was thoroughly assessed and classified into vascular, cardiac and renal OD. Primary endpoints were major adverse cerebrocardiovascular events (MACCE) and all-cause mortality. Results Nine hundred seventy-eight participants out of 3234 participants (43.1%) were identified as having NSS HVA. The NSS HVA group exhibited a younger age, lower blood pressure levels, lower body mass index, and milder OD compared to the non-NSS HVA group. Over follow-up of 5.7 ± 1.8 years, 332 MACCE (1.82 per 100 person-year) and 212 all-cause deaths (1.14 per 100 person -year) occurred. NSS HVA was associated with a reduced risk of MACCE (HR [95% CI] = 0.585, 0.454–0.754) and all-cause death (HR [95%CI] = 0.608 [0.445, 0.832]), especially in those subgroups without clinical diagnosed cardiovascular disease (CVD) or diabetes mellitus but with at least one type of OD. Moreover, NSS HVA exhibited improved prognostic value for MACCE, all-cause death and CVD death compared to other definitions of HVA. Conclusions Age and blood pressure stratified NSS HVA could serve as an improved indicator against serious adverse events in the community-dwelling elderly Chinese. Trial registration Prognosis in the Elderly Chinese: The Northern Shanghai Study (NSS), NCT02368938, https://clinicaltrials.gov/study/NCT02368938?cond=NCT02368938&rank=1 .